The Effectiveness of the Implementation of Batam City Regional Regulation No. 11 of 2013: A Study on Waste Management (2024–October 2025) - Utomo, Achmad Aji Setyo; Jaya, Febri; Ampuan Situmeang (Sean Institute, 2026)
Waste management issues in Batam City have become a critical environmental concern amid rapid population growth and intensive industrial activities. Although the Batam City Government has enacted Regional Regulation Number 11 of 2013 on Waste Management as a legal framework, its implementation in practice continues to face significant challenges. This study aims to analyse the effectiveness of the regulation and its legal implementation during the period 2024–2025, as well as to identify the inhibiting factors affecting its enforcement. The research employs an empirical legal method using statutory and sociological approaches, supported by interviews with officials from the Environmental Agency and officers at the Telaga Punggur Final Disposal Site (TPA). The findings indicate that the effectiveness of the regulation remains low due to weak law enforcement, limited infrastructure and facilities such as waste collection fleets and heavy equipment and low public awareness regarding waste segregation and management. Based on Soerjono Soekanto’s theory of legal effectiveness, these constraints are closely related to law enforcement actors, supporting facilities, and the legal culture of the community. This study recommends strengthening regulatory enforcement, upgrading waste management facilities, enhancing public education, and fostering synergy among government, communities, and the private sector to achieve an effective and sustainable waste management system in Batam City.